INCREASING TEACHER CAPACITY IN PREPARING LEARNING IMPLEMENTATION PLANS (RPP) FOR THE 2013 CURRICULUM THROUGH GROUP TECHNICAL ACADEMIC SUPERVISION IN TASIKMALAYA CITY ASSISTED SCHOOLS (MTSS ATTARBIYAH AND MTSS BAITUL HIKMAH) IN 2019 - Neneng Sugiartini (Journal Civics And Social Studies, 2022)
This school action research was motivated by the fact that at MTsS Attarbiyah Tasikmalaya City, of the 36 teachers, only 10 (27.78%) were able to prepare the RPP for Curriculum 13, the remaining 26 people (72.22%) had not been able to prepare the RPP for Curriculum 2013. At MTsS Baitul Hikmah Tasikmalaya City, of the 26 teachers, only 6 (23.08%) were able to prepare (RPP) for the 2013 Curriculum, the remaining 20 (76.92) people had not been able to prepare the RPP for the 2013 Curriculum. This was caused by various things including : (1) teachers' understanding of the preparation of the 2013 Curriculum (RPP) is still lacking; (2) guidance for teachers in preparing the 2013 Curriculum (RPP) has not been optimal (3) most teachers have never participated in workshops on preparing the 2013 Curriculum (RPP); (4) lack of resources that teachers have regarding preparation techniques (RPP) for the 2013 Curriculum; (5) The RPP that teachers have is generally not the product of the teacher himself. This school action research is limited to the problem "School supervisors' efforts to improve teachers' abilities in preparing the 2013 Curriculum (RPP) through group technical academic supervision in two target schools". The aim of this school action research is to improve teachers' abilities in preparing the 2013 Curriculum (RPP) through group technical academic supervision in two target schools. The framework of thinking in this school action research is: (1) High teacher ability influences improving the quality of learning. The increasing ability of teachers in preparing the 2013 Curriculum (RPP) will further improve the quality of character-based learning; (2) Academic supervision will encourage teacher professional improvement. The better the teacher's performance through academic supervision, the greater the teacher's professionalism will be. The more professional teachers will encourage improvements in the quality of learning. Based on the results of the School Action Research conducted by researchers on teachers at MTsS Attarbiyah Kota Tasikmalaya and MTsS Baitul Hikmah Kota to increase teacher competence in preparing the 2013 Curriculum (RPP) through group technical academic supervision with variations between classical and individual group guidance, it can be concluded that there is an increase in ability teachers who were significant in compiling (RPP) Curriculum 2013. This can be seen from the increase in all observation indicators from cycle I to cycle II, which at the end of cycle II all teachers were able to compose (RPP) Curriculum 2013 in accordance with applicable regulations, values Character values ​​appear in learning objectives and learning indicators, character values ​​appear in the learning process, and character values ​​emerge in exploration, elaboration and confirmation activities.